Solvatofluorochromism and twisted intramolecular charge-transfer state of the nile red dye - Ya. Freidzon, Alexandra; Safonov, Andrei A.; Bagaturyants, Alexander A.; Alfimov, Michael V. (International journal of quantum chemistry, 2012)
Profiles of the S1 potential energy surface of the Nile Red dye along the rotational coordinate of the amino group are computed using time‐dependent density functional theory (TDDFT) and XMCQDPT2/CASSCF. The calculated profiles exhibit two minima corresponding to a planar locally excited (LE) state and a twisted intramolecular charge transfer (TICT) state. The profiles calculated by time‐dependent density functional theory (TDDFT) depend on the weight of the hartree‐fock (HF) exchange in the functional: at 0% exchange, only the TICT minimum exists, whereas at 50% exchange and more there is only the LE minimum. The profiles obtained by TDDFT at 20–25% HF exchange are in qualitative agreement with that obtained by XMCQDPT2/CASSCF calculations. The energy of the charge transfer state is lowered due to the participation of doubly excited configurations and dynamic correlations, which is implicitly included in the density functionals. The solvent effects on the relative energies of the LE and TICT states and on the barrier height are studied using the polarizable continuum model. The effect of hydrogen bonds is studied for a complex of Nile Red with two water molecules. The solvatochromism of Nile Red fluorescence in aprotic polar solvents is explained by nonspecific solvation, which stabilizes the LE state and causes Nile Red fluorescence solvatochromism; in water and alcohols, it is explained by the formation of hydrogen bonds, which stabilize the TICT state and facilitate the LE‐to‐TICT transition. © 2012 Wiley Periodicals, Inc. The fluorescence of the Nile Red dye is highly sensitive to the environment. Time‐dependent DFT and second‐order multireference perturbation theory show that the S1 state of Nile Red has two minima, one corresponding to planar locally excited and the other to twisted intramolecular charge‐transfer states. The solvatofluorochromism of Nile Red is explained by the effect of nonspecific solvation in aprotic solvents or hydrogen bonding in protic solvents on both minima and on the barrier height.